Effect of elastic deformation on lubrication characteristics in different clearances and head size of metallic artificial hip joint - Harun, Muhamad Noor; Mohd Suri, Mohd Syafiq; Mohd Yusof, Ab Aziz; Syahrom, Ardiyansyah; Abd. Latif, Mohd Juzaila (SAGE Publications Ltd, 2024)
The issue of lubrication in metallic artificial hip joints is discussed to prevent the two bearing surfaces from contacting each other. This study aims to analyse the characteristics of elastohydrodynamic lubrication (EHL) and investigate the effect of radial clearance and head size on the tribological performance of metallic artificial hip joints under steady-state conditions using the Fluid-Structure-Interaction (FSI) method. The average load in the z-direction and flexion-extension motion around the y-axis were used to represent normal walking. This study demonstrates that the film thickness profile from the validation study aligns with the findings of the previous study. The contour of the fluid pressure in the central contact zone changes with different time steps – the direction of fluid movement corresponds to the solid-fluid reaction. Additionally, the deformation of the cup surfaces contributes to the continuous fluid film that separates the contact surfaces. Furthermore, design parameters also influence EHL performance. It has been discovered that less radial clearance and a larger head size led to an increase in fluid film thickness